Path Analysis on the Biopsychosocial Determinants of Quality of Life among Children with Cerebral Palsy - Ramadhani, Alinda Nur; Adriani, Rita Benya; Salimo, Harsono (Journal of Maternal and Child Health, 2018)
Background: Cerebral palsy(CP) is group of disorders characterized by long-term disabilities that affect thequality of life(QoL) of both patients and those caring for them. This study aimed to examine biopsychosocial determinants of quality of life among children with cerebral palsy, using path analysis model.Subjects and Method: A cross-sectional study was conducted at Fondation for the Care of Disable Children (YPAC) and Pediatric Neurodevelopmental Therapy Center, Surakarta, Central Java, from April to May 2018. A sample of 110 children with cerebral palsy was selected for this study by simple random sampling. The dependent variable was quality of life. The independent variables were gross motoric skill, parental stress, family support, and social support. Data on quality of life was measured by Cerebral Palsy Quality of Life (CP-QOL) questionnaire. The other data were collected by questionnaire and analyzed by path analysis.Results: Quality of life of children with cerebral palsy increased with better gross motor (b= 2.79; 95% CI= 1.54 to 4.03; p<0.001), strong family support (b=1.25; 95% CI= 0.26 to 2.24; p= 0.013), and strong social support (b= 0.99; 95% CI= 0.014 to 1.97; p= 0.047). Quality of life of children with cerebral palsy indirectly decreased with high parental stress (b= -1.55; 95% CI= -2.38 to -0.72; p<0.001).Conclusion: Quality of life of children with cerebral palsy increases with better gross motor, strong family support, and strong social support, but indirectly decreases with high parental stress.Keywords: cerebral palsy, quality of life, gross motor, family support, parental stress, childrenCorrespondence:Alinda Nur Ramadhani. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java. Email: aramadhani95@gmail.comJournal of Maternal and Child Health (2018), 3(4): 301-307<br/p>https://doi.org/10.26911/thejmch.2018.03.04.08